Peran keluarga dalam merawat orang dengan gangguan jiwa: A scoping review - Hendrawati Hendrawati; Iceu Amira; Nina Sumarni; Udin Rosidin; Indra Maulana (Holistik Jurnal Kesehatan, 2023)
Background: Mental disorders often occur in society and are diseases characterized by disturbed emotions, behavior and thoughts that are not logically related. The family is the smallest unit in society and plays a very important role in the healing process for clients with mental disorders. Family experiences in caring for clients with mental disorders often face problems of anxiety, confusion, and daily parenting difficulties.Purpose: To determine the role of the family in caring for people with mental disorders, it is necessary to have a new review that discusses evidence based on the role of the family in caring for people with mental disorders.Method: This research uses a scoping review design which aims to explore the role of the family in providing care for family members with mental disorders. The year range used in searching for scientific articles was 10 years (2013-2022), and researchers used the PRISMA flow diagram study selection guide to assess the quality of research articles.Results: The results of a search for articles regarding the role of the family in caring for ODGJ, found 4 articles discussing the role of the family in caring for ODGJ, 6 articles discussing the burden on families caring for ODGJ, 1 article discussing family burden factors in caring for ODGJ, and 4 articles discussing the support provided necessary to improve the quality of life of families caring for ODGJ.Conclusion: There are many roles for families in caring for ODGJ and there are various useful applications in families to improve care for ODGJ.Keywords: Family; Mental Disorders; Roles.Pendahuluan: Gangguan jiwasering terjadi di masyarakat dan merupakan penyakityang ditandai dengan emosi, perilaku dan pikiran terganggu yang tidak berhubungan secara logis. Keluarga adalah unit terkecil dalam masyarakat,dan sangatberperan dalam proses penyembuhan klien dengan gangguan jiwa. Pengalaman Keluarga dalammerawat klien gangguan kejiwaan sering menghadapi dengan masalahkecemasan, kebingungan dan kesulitan pengasuhan sehari-hari.Tujuan: Untuk mengetahui peran keluarga dalam merawat orang dengan gangguan jiwa, diperlukan adanya suatu review terbaru yang membahas tentang evidence based terkait peran keluarga dalam merawat orang dengan gangguan jiwa.Metode: Penelitian ini menggunakan desain scoping review yang bertujuan untuk mengeksplorasi peran keluarga dalam pemberian perawatan bagi anggota keluarga dengan gangguan jiwa. Rentang tahun yang digunakan dalam pencarian artikel ilmiah adalah 10 tahun (2013-2022), dan peneliti menggunakan panduan penyeleksian studi PRISMA flow diagram untuk melakukan penilaian kualitas artikel penelitian.Hasil: Penelusuran artikel mengenai peran keluarga dalam merawat ODGJ, didapatkan 4 artikel yang membahas peran keluarga dalam merawat ODGJ, 6 artikel membahas beban keluarga yang merawat ODGJ, 1 artikel yang membahas faktor beban keluarga dalam merawat ODGJ, dan 4 artikel yang membahas dukungan yang diperlukan untuk meningkatkan kualitas hidup keluarga yang merawat ODGJ.Simpulan: Banyak peran keluarga dalam merawat ODGJ dan adanya berbagai penerapan yang berguna dalam keluarga untuk meningkatkan perawatan pada ODGJ.